Chiral poly(L-lactic acid) driven helical self-assembly of oligo(p-phenylenevinylene) - Nisha, S. Kumari; Asha, S. K. (Journal of Materials Chemistry C, 2014)
The synthesis and self-assembly of a series of copolyesters incorporating varying mol ratios of an achiral oligo(p-phenylenevinylene) (OPV) into the backbone of a chiral poly(L-lactic acid) (PLLA) via high temperature solution blending is reported. The polymers were characterized by H-1 NMR spectroscopy and size exclusion chromatography (SEC) and their bulk properties were investigated by differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WXRD). The DSC and WXRD analyses confirmed the crystallinity and pi-pi stacking of the OPV units in the PLLA-OPV copolyester. Absorption, emission and lifetime-decay studies showed that the OPV chromophore was highly aggregated in the solid state. The solid powder samples of the copolyesters exhibited an intense, red shifted aggregate emission beyond 470 nm. Circular dichroism (CD) spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies revealed that the PLLA-OPV copolyester formed a self-assembled architecture, in which the helical organization of the achiral OPV segments was dictated by the chiral PLLA segments. The observed CD signal and AFM image accounted for the right-handed helical self-assembly of the OPV chromophore in the solid state. These results confirmed the effect of the chiral PLLA segment on tuning the OPV chromophore packing and supramolecular chirality in molecular aggregates. The methodology illustrated here provides opportunities for the design of a new class of hierarchical, self-assembled architectures, based on organic pi-conjugated materials and the manipulation of their optical properties.